Torsional Behavior of Reinforced Concrete T Beams Strengthened with CFRP Strips - Ban S. Abduljalil; Kaiss F. Sarsam (Engineering and Technology Journal, 2012)
This work aims at studying the strengthening of T beams in torsion by using carbon fiber reinforced polymer (CFRP). The experimental work includes investigation of five reinforced concrete T beams tested under pure torsion. Variables considered in the test program include; effect of flange strengthening, effect of fiber orientation (90º or 45º CFRP strips with respect to the beam longitudinal axis), and the effect of using additional longitudinal CFRP strips with transverse CFRP strips. Test results were discussed based on torque - twist behavior, beam elongations, CFRP strain, and influence of CFRP on cracking torque, ultimate torque and failure modes. Results indicate significant increases in ultimate torque capacity with the use of CFRP.